Pengaruh Budaya Terhadap Desain Web Menggunakan Pendekatan Hofstede - Sodik, Anwar; Putri, Rahmi Rizkiana (INTEGER: Journal of Information Technology, 2019)
The development of the website as a media is growing rapidly. Both in quality and quantity. Culture is a way of life from humans that will affect the work of humans, including website as human’s creation. Culture is composed of technology, values and society. This research will evidence at how the influence of culture on a website, both visual and non-visual. This study use the Hofstede framework that uses 6 parameters ; Power Distance, Individualism, Masculinity, Uncertainty Avoidance, Long Term Orientation, and Indulgence. Case studies in this study are the Indonesian Red Cross website and the British Red Cross website. The results of this study it can be concluded that the culture of a country influences on the  website design. So website design is a reflection of culture and history of that country.